The trade : my journey into the labyrinth of political kidnapping - Van Dyk, Jere (Public Affairs, an imprint of Perseus Books, LLC, a subsidiary of Hachette Book Group, Inc., 2017)
In 2008, American journalist Jere Van Dyk was kidnapped and held for 45 days. At the time, he had no idea who his kidnappers were. They demanded a ransom and the release of three of their comrades from Guantanamo, yet they hinted at their ties to Pakistan and to the Haqqani network, a uniquely powerful group that now holds the balance of power in large parts of Afghanistan and the tribal areas of Pakistan. After his release, Van Dyk wrote a book about his capture and what it took to survive in this most hostile of circumstances. Yet he never answered the fundamental questions that his kidnapping raised: Why was he taken? Why was he released? And who saved his life? Every kidnapping is a labyrinth in which the certainties of good and bad, light and dark are merged in the quiet dialogues and secret handshakes that accompany a release or a brutal fatality. In The Trade, Jere Van Dyk uses the sinuous path of his own kidnapping to explain the recent rise in the taking of Western hostages across the greater Middle East. He discovers that he was probably not taken by the anonymous "Taliban," as he thought, but by the very people who helped arrange his trip and then bargained for his release. It was not a matter of chance: CBS, Van Dyk's employer at the time, launched a secret rescue and, he learned later, paid an undisclosed ransom to a tribal chief who controlled the area in which he was kidnapped and who delivered him and his guide safely to a US Army base. In 2013, Van Dyk returned to the Middle East to unravel the links among jihadist groups, specifically that of the Haqqani network. His investigation finally paid off in 2015, when Van Dyk was taken to a discreet room in a guesthouse in Islamabad where he met Ibrahim Haqqani, part of the leadership of the Haqqani network who has been seen by very few outsiders since 9/11. There, Van Dyk learned of the Haqqanis' links to Pakistan, Saudi Arabia, the ISI, and the CIA and their involvement in the kidnapping of Bowe Bergdahl and many others. Back in the United States, Van Dyk saw the other side of the kidnapping labyrinth as he became involved with other former hostages and the families of recent kidnapping victims murdered by the Islamic State. Van Dyk's investigation shows how America's foreign policy strategy, the terrible cynicism of the kidnappers, and a world of shadowy interlocutors who play both sides of many bargains combine to create a brutal business out of the exchange of individual human lives for vast sums of money --